2012
DOI: 10.1007/s00213-011-2621-9
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and white matter microstructure

Abstract: Rationale Diffusion tensor imaging has been used before in testing associations between cigarette smoking and white matter integrity, with inconsistent results. Published reports indicate higher fractional anisotropy (FA) in some brain regions and lower FA in others in adult smokers compared to nonsmokers. Adolescent smokers exhibited elevated FA at several sites and a positive correlation of FA in the genu corpus callosum with exposure to smoking (pack-years). Objective To help resolve prior discrepancies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 47 publications
(67 reference statements)
4
80
2
Order By: Relevance
“…The nicotine-induced cytotoxic swelling suggested by Gazdzinski et al (22) and proinflammatory effects of cigarette smoke on tissue as shown by elevated peripheral leukocytes, and recruitment of polymorphonuclear cells, monocytes, macrophages, and increased fibrinogen may be partly responsible for cellular edema and reduced MD levels in the H S of the current study (23). Some recent studies have hypothesized on the neurotropic and promyelinating effects of smoking and have found higher FA in brain regions such as the prefrontal WM, cingulum, and corpus callosum in smokers compared with nonsmokers (9,24). Yet, another study on heavy smokers reported decreased FA in the anterior corpus callosum (25).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The nicotine-induced cytotoxic swelling suggested by Gazdzinski et al (22) and proinflammatory effects of cigarette smoke on tissue as shown by elevated peripheral leukocytes, and recruitment of polymorphonuclear cells, monocytes, macrophages, and increased fibrinogen may be partly responsible for cellular edema and reduced MD levels in the H S of the current study (23). Some recent studies have hypothesized on the neurotropic and promyelinating effects of smoking and have found higher FA in brain regions such as the prefrontal WM, cingulum, and corpus callosum in smokers compared with nonsmokers (9,24). Yet, another study on heavy smokers reported decreased FA in the anterior corpus callosum (25).…”
Section: Discussionmentioning
confidence: 54%
“…The variable degrees of addiction of smoking in the participants might be one important factor in these contradictory research findings. Although limited dependence and exposure to nicotine revealed no significant change, heavy smoking exposure showed marked FA reductions in WM (9,24). Whether FA or MD is more sensitive and an earlier measure of WM disintegrity remains controversial in the literature (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…(2011) revealed a reduction in the microstructural integrity of the cerebral WM in cigarette smokers. Changes in DTI findings related to smoking behavior have been demonstrated in multiple regions, including the corpus callosum, internal capsule, and prefrontal WM at multiple levels (Hudkins, O'Neill, Tobias, Bartzokis, & London, 2012; Paul et al., 2008; Zhang, Stein, & Hong, 2010). In our study, after controlling for the number of pack years of smoking, there was no observable group difference in the ADC in the posterior corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, DTI measures were correlated with cannabis use measures in the cannabis user group only. All white matter integrity analyses included covariates of age, gender, education, IQ, alcohol and cigarette consumption since these variables have known associations with white matter integrity (Szeszko et al 2003;Lebel et al 2008;Pfefferbaum et al 2009;Hudkins et al 2012). Given the unequal tobacco use between groups, we conducted additional partial analysis of models to assess for confounding of tobacco use which is presented in the supplemental information.…”
Section: Discussionmentioning
confidence: 99%